Dinamika Pemilihan Kepala Daerah Berdasarkan Peraturan Perundang–Undangan di Indonesia - Muslimin, Husein (Jurnal Cakrawala Hukum, 2019)
Direct regional head election, with Law Number 32 Year 2004 the regional head election starts from the determination of candidates proposed by political parties or a combination of political parties in pairs with their representative candidates to be elected directly by the people in the area concerned. The counting system is considered to be less representative because of the candidateâ€™s dependence on the party or party combination, then through Law Number 12 Year 2008 as the second amendment to Law Number 32 Year 2004 provides the opportunity for candidate pairs from individuals with certain conditions, this system requires large costs and drains â€˜energy, money politics also occur even bigger because the target is the people as voters. Weaknesses in the law are then sought to be overcome through Law Number 8 of 2015 by determining one round of elections, the prohibition of political parties or a combination of political parties to accept all the dowry from the candidate pairs promoted, and the conception of regional head elections simultaneously nationally. How to cite item:Â Muslimin, H. (2019). Dinamika Pemilihan Kepala Daerah Berdasarkan Peraturan Perundangâ€“Undangan di Indonesia.Â Jurnal Cakrawala Hukum, 10(1), 40-49. doi:https://doi.org/10.26905/idjch.v10i1.3187